Upward elevational shift by breeding Whinchat Saxicola rubetra in response to cessation of grazing in upland grassland. Issue 1 (2nd January 2021) - Calladine, John; Jarrett, David
ABSTRACT: Capsule: The distribution of breeding Whinchats Saxicola rubetra shifted uphill following the cessation of grazing, potentially compromising their breeding success through additional squeezing of suitable habitat and environmental niches. Aims: To assess whether breeding territories occupied by a conservation-priority grassland bird followed changes in sward structure associated with environmental exposure following cessation of grazing. Methods: Whinchat territories and breeding success were monitored at upland study sites in Scotland during a period of habitat transformation from livestock-grazed grassland to young woodland with herbivores excluded. Results: After grazing was excluded, there was generally an upwards elevational shift of breeding attempts by Whinchats (by 43 m in 7 years at one site). While the study sites were grazed, breeding attempts were more successful at lower elevations. After grazing ceased, there was lower breeding success at lower elevations where the resulting taller, denser vegetation likely restricted available foraging habitat. Despite that, lower areas continued to be occupied by territorial Whinchats. Conclusions: The conservation of grassland birds within afforestation schemes could be supported by the maintenance of some open habitats at suitable elevations. However wider conservation of grassland birds, including within forested and pastoral high nature value farmed landscapes would benefit from a better understanding of the mechanisms operating on breeding success and habitat choice within these dynamically changing habitats.